STRATEGI PEMASARAN USAHA MIKRO CITRONG (CHEESE STICK TERONG) KELOMPOK WANITA TANI MENTARI BINAAN ORGANISASI IAAS LC UNPAD - Lusi Wulan Safitri (Jurnal Perilaku dan Strategi Bisnis, 2020)
Genteng village's potential in agriculture sector is dominated by various vegetables commodities, one of which is eggplant. The Village Concept Program that was held in 2016 have been successful on creating a collaboration between IAAS LC Unpad and Kelompok Wanita Tani Mentari, which is a snack called Citrong with eggplant as it's main ingredient. The development of Citrong as a micro business doesn't always go as planned, because Kelompok Wanita Tani Mentari still can't market this product. So, marketing strategy is needed. This research aims to create a marketing strategy of Citrong micro business for Kelompok Wanita Tani Mentari. This research use qualitative design with study case as research technique. IFAS, EFAS, IE, and QSPM matrix are used for data analysis. The results of this research is micro business of Citrong in cell II (average internal position and high external position) which shows the type of strategy “Growth and Build”. So,marketing strategy that can be applied are intensive strategies such as market penetration, market development, and product development or integrated strategies such as backward integration, forward integration and horizontal integration.Keywords : Citrong, Marketing Strategy, Micro Business